Increased Understanding of Legal Aid for Residents of Pondok Bambu Detention Center in Facing Trial in Court - Heru Sugiyono; Wicipto Setiadi; Aji Lukman Ibrahim (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Rutan Pondok Bambu is one of the technical implementation units of the Ministry of Law and Human Rights of the Republic of Indonesia under the directorate general of corrections. Rutan Class I Pondok Bambu was established in 1974 by the Regional Government or DKI Jakarta Regional Government which consists of the Orchid Pavilion with a total of 18 (eighteen) residential rooms which are female residents with criminal cases. Related to the understanding of legal aid, the State has an obligation to realize the implementation of a fair judiciary by guaranteeing the creation of a situation where each individual has the right to get a justice, which, among others, is carried out by providing legal assistance in the form of legal assistance and consultation related to civil, criminal and administrative issues, both in litigation and non-litigation as stipulated in  Law Number 16 of 2011 concerning Legal Aid. Although legal aid has been regulated in the laws and regulations, there are still many assisted residents in Rutan Klas 1 Pondok Bambu who do not know and understand it. This is then the reason behind the implementation of Community Service at Rutan Klas 1 Pondok Bambu. The implementation method is carried out through a process of dialogue with the target residents / community and discussions in counseling activities, after the delivery of the material, a question and answer is held. All activities are carried out by taking into account administrative order, so that each activity must obtain a permit and be recorded at the Klas I Pondok Bambu Detention Center which is a partner in the implementation of this community service.